Full linearization of nonlinear flow control valves via variable gear ratio design - Thitipun Thongnueakhaeng; Tawat De Haas; Thananchai Leephakpreeda (Scientific Reports)
Abstract The paper proposes the full linearization of nonlinear characteristics of flow control valves via variable gear ratio design. The inherent nonlinear function of the normalized valve capacity coefficients to the percentages of valve opening is derived from flow experiments. In analysis, it is found that the derivative of the inverse function is the reciprocal of the gear ratio, which is used to generate the corresponding driving/driven gear profiles. The rotation of the driven stem of the flow control valve from a driving knob is altered by the variable gear ratio to achieve fully linearized flow characteristics. The experimental results confirm the fully linearized characteristics of a conventional nonlinear flow control valve with correlation to the linearity with R-squared = 0.9984.